27. CLINICAL OUTCOMES OF 375 PATIENTS UNDERGOING MINI-PERCUTANEOUS NEPHROLITHOTOMY WITH CAMERA GUIDANCE AT TRANSPORT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical and paraclinical characteristics, treatment outcomes, and complications in patients with urolithiasis managed by mini-percutaneous nephrolithotomy (mini-PCNL) using camera guidance at Transport Hospital.Methods: A cross-sectional study was conducted on 375 patients with urolithiasis treated at Transport Hospital from January 2022 to December 2024. Variables collected included age, sex, occupation, dietary habits, stone characteristics, treatment outcomes, and postoperative complications. Data were analyzed using descriptive statistics and comparative analysis between patients with few stones and those with multiple stones.Results: Male patients accounted for the majority (62.1%), with a mean age of 51.3 ± 12.4 years. Multiple stones were more common in older males with sedentary occupations and low water intake (p < 0.05). The overall stone-free rate was 86.9%. Complications occurred in 7.2% of cases, mostly mild (fever, transient bleeding), with no severe complications recorded. These outcomes are consistent with national and international reports, confirming the efficacy and safety of the technique.Conclusion: Retrograde ureteroscopic lithotripsy using a miniature camera combined with Holmium laser is a safe and effective method for the treatment of urolithiasis. In addition to surgical intervention, preventive measures and lifestyle modifications are essential to reduce recurrence and improve long-term patient outcomes in the community.
Keywords: Urolithiasis; Retrograde ureteroscopy; Holmium laser; Miniature camera